Coordinate-wise Prescribed-time Stabilization in Block Control Form. Issue 9 (2022) - Utkin, Vadim; Orlov, Yury
Abstract: Dynamic systems with finite time convergence have been studied intensively in numerous publications on sliding mode control, systems with terminal control, systems with homogeneity properties. Recently research has been initiated for a new class of such systems with remarkable property -finite time convergence does not depend on initial conditions. The main attention was initially paid to SISO systems in canonical form (chain of n integrators). The paper demonstrates that the method can be generalized for MIMO systems in the block control form, consisting of a set of lower order systems with dimension equal to the dimension of intermediate controls. First it is shown that the design procedure let the designer decouple systems in canonical form into set of problems of the first order. Dealing with non-autonomous linear systems is another novelty of the presented investigation.